STABILITAS FISIK DAN MUTU HEDONIK SIRUP DARI BAHAN TEMULAWAK (Curcuma xanthorrhiza Roxb.) - Nutrisia Aquariushinta Sayuti; Agus Winarso (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2014)
ABSTRACT Curcuma  xanthorrhiza  that  contain  of  curcumin  and  essential  oil  make  the  taste  isn’t delicious. Syrup form can  cover the lack of the flavor. The study aimed to describe the results of the physical stability test and hedonic test  of Curcuma syrup. It  was an experimental research by analyzing  the  physical stability and hedonic quality of Curcuma syrup. Physical stability test was done  by  storing  the  syrup  at  a  temperature  of  400C  for  8  weeks,  analyzing  the  organoleptic, viscosity  and  acidity  (pH)  every  2  weeks.  55  of  4th semester  students,  Jamu  Department, Polytechnic of Surakarta, 2014/2015  act as a semi-trained panelists in a hedonic test. The results concluded that the viscosity of syrup which was originally ± 190 mP.as decreased in storage for 2 weeks  to ± 170 mP.as and  finally stabilized  to week 8th. The acidity degree   stable at pH 4. The   organoleptics were  no  change,    it  was  brownish  yellow,  a  distinctive  smell  of  curcuma,  citrus flavor    and  texture  rather  thick.  The  panelists’  assessment  against  the  syrup  was  70.91%  of panelists liked the scent, 78.18% of panelists liked the taste, 85.46% of panelists liked the  texture and 83.64% panelists liked  the color of syrup. Keywords: Curcuma, Syrup, physical stability, hedonic